A feasibility study on using virtual reality for understanding deficiencies of high school students - Manouchou, Elena; Stavroulia, Kalliopi Evangelia; Ruiz-Harisiou, Antri; Georgiou, Kyriakos; Sella, Francesca; Lanitis, Andreas (My University, 2016)
A significant number of high school students face different types of problems that prevent them from attending adequately classes. On the other hand teachers are faced with the daunting task of identifying and addressing problems faced by students. Correcting actions towards student deficiencies imply that teachers are able to fully understand the implications on student activities caused by different types of problems. In this paper we describe a feasibility study that aims to assess the potential of using Virtual Reality as a tool for training teachers to fully understand the difficulties of students suffering from different types of deficiencies. As part of the proposed work, teachers are given the opportunity to participate in a virtual class in the role of students that face certain deficiencies allowing them to experience problems faced by students so that teachers learn how to deal effectively with such cases in real classrooms. In our preliminary investigation we concentrated our attention on the problem of myopia so that teachers who participated in the experiment had the opportunity to attend a class as visually impaired persons. The results of this preliminary investigation indicate that teachers who participated in the experiment showed increased awareness and understanding of the problem. Furthermore, the results revealed the potential of such application for teacher training.
Keywords: Teacher training; Vision disorders; Virtual learning environments